Dietary supplementation of high-performance Korean and Japanese judoists - Kim, J.; Lee, N.; Lee, J.; Jung, S.-S.; Kang, S.-K.; Yoon, J.-D. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
This research investigated patterns of the use of dietary supplement and doping awareness among high-ranked judoists from 2 countries. Korean (70 men and 31 women) and Japanese (37 men and 34 women) national judo team members were divided into 2 groups (high and low competitive performance levels) according to their international and national rankings. Fifty-nine percent of Korean and 61% of Japanese judoists consumed dietary supplements. Eighty-eight percent of high- and 51% of low-competitive-performance-level Korean judoists consumed dietary supplements. Sixty-eight percent of high- and 57% of low-competitiveperformance- level Japanese judoists consumed dietary supplements. Oriental supplements (34%), vitamins (23%), and protein powder (12%) were the most commonly consumed dietary supplements in Korean judoists. Vitamins (45%), protein powder (33%), and minerals (15%) were the most commonly consumed dietary supplements in Japanese judoists. Thirty-eight percent of judoists from both countries had not received any proper education about antidoping, and 44% of judoists from both countries had not received knowledge of antidoping legislation. There was a significant difference in education about antidoping between high and low competitive-performance levels of Korean judoists (p < .001). Korean judoists received significantly less antidoping education than Japanese judoists (p < .001). The associations for antidoping education and knowledge of antidoping legislation with the use of dietary supplements were 3.46 (95% CI = 1.31-9.12) and 1.63 (95% CI = 0.71-3.76), respectively. Our findings showed that use of dietary supplements in judoists from both countries was increased after experiencing antidoping education.